Math in Pokemon: Gotta Catch 'Em All!

Calculus Level 4

While playing Pokémon Go! on his mobile device, Ash Ketchum walks toward the round fountain and sees if he can catch as many Pokémons as he can, so he can trade some with his friends.

Starting at the point ( 3 , 0 ) (3,0) on the circle whose equation is x 2 + y 2 = 9 x^2 + y^2 = 9 , he walks 2 π n \frac{2\pi}{n} meters along the circumference to catch a Pokémon for each n th n^\text{th} step, such that

  • for odd n n , he walks counterclockwise;
  • for even n n , he walks clockwise.

What is the final displacement (after walking infinite steps) in meters Ash has traveled from ( 3 , 0 ) (3,0) ? If your answer is of the following form: B B cos ( C π D ln ( E ) ) , \sqrt{B - B\cos\left(\dfrac{C\pi}{D}\ln(E)\right)}, where B , C , D , E B,C,D,E are integers, gcd ( C , D ) = 1 \gcd(C,D)=1 , and E E is natural-log-free, find B + C + D + E B + C + D + E .


Image Credit: Tallahassee Democrat


The answer is 25.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

First Last
Dec 10, 2016

The amount of distance walked can be represented as the absolute value of the alternating harmonic series n = 1 ( 1 ) n 2 π n = 2 π ln 2 \displaystyle \big| \sum_{n=1}^{\infty}\frac{(-1)^n2\pi}{n}\big| = 2\pi\ln{2}

We find the angle θ \theta by arc length circumference × 2 π = 2 π ln 2 3 π \displaystyle\frac{\text{arc length}}{\text{circumference}}\times 2\pi = \frac{2\pi\ln{2}}{3\pi}

Now using the Law of Cosines the green distance D = 2 3 2 2 3 2 cos ( 2 π ln 2 3 ) \displaystyle D = \sqrt{2*3^2-2*3^2\cos{(\frac{2\pi\ln{2}}{3})}}

25 \Huge\boxed{25}

Sweet solution! :D

Michael Huang - 4 years, 6 months ago
Michael Huang
Dec 8, 2016

Calculus

In polar coordinates, x 2 + y 2 = 9 r = 3 x^2 + y^2 = 9 \quad \Longleftrightarrow \quad r = 3 Define a "step" as one counterclockwise-clockwise travel successively. It is clear that

  • Counter-clockwise steps increase the arc length between the given and arriving points.
  • Clockwise steps decrease the arc length between the given and arriving points.

Let θ d \theta_d denote the final point (relative to the origin) after infinite steps. Since Ash starts at the point ( 3 , 0 ) (3,0) , it is clear that θ = 0 \theta = 0 (also relative to the origin). By the polar-coordinate formula of the arc length , the net arc distance traveled is 0 θ d r 2 + ( d r d θ ) 2 d θ = 0 θ d 3 2 + 0 2 d θ = 0 θ d 3 d θ = 3 θ d \begin{array}{rl} \int\limits_0^{\theta_d} \sqrt{r^2 + \left(\dfrac{dr}{d\theta}\right)^2}\,d\theta &= \int\limits_0^{\theta_d} \sqrt{3^2 + 0^2}\,d\theta\\ &= \int\limits_0^{\theta_d} 3\,d\theta\\ &= 3\theta_d \end{array} Since the net arc distance traveled alternates between two different directions, the summation is 2 π n = 2 π ( n odd 1 n n even 1 n ) \sum \dfrac{2\pi}{n} = 2\pi\left(\sum\limits_{n\text{ odd}}^{\infty} \dfrac{1}{n} - \sum\limits_{n\text{ even}}^{\infty} \dfrac{1}{n}\right) which is equivalent to 2 π n = 1 ( 1 ) n + 1 n 2\pi\sum\limits_{n = 1}^{\infty} \dfrac{(-1)^{n + 1}}{n} By the following Maclaurin series ln ( 1 + x ) = n = 1 ( 1 ) n + 1 x n n \ln(1 + x) = \sum\limits_{n = 1}^{\infty} \dfrac{(-1)^{n + 1}x^n}{n} where x = 1 x = 1 , 2 π n = 1 ( 1 ) n + 1 n = 2 π ln ( 2 ) 2\pi\sum\limits_{n = 1}^{\infty} \dfrac{(-1)^{n + 1}}{n} = 2\pi\ln(2) So 3 θ d = 2 π ln ( 2 ) θ d = 2 π 3 ln ( 2 ) 3\theta_d = 2\pi\ln(2) \quad \Longrightarrow \quad \theta_d = \dfrac{2\pi}{3}\ln(2)


Determining the Final Displacement

For θ d \theta_d , let ( x d , y d ) (x_d,y_d) be the final point on x 2 + y 2 = 9 x^2 + y^2 = 9 . In Cartesian coordinates, θ d = arctan ( y d x d ) = 2 π 3 ln ( 2 ) y d x d = tan ( 2 π 3 ln ( 2 ) ) y d = tan ( 2 π 3 ln ( 2 ) ) x d \begin{array}{rl} \theta_d = \arctan\left(\dfrac{y_d}{x_d}\right) &= \dfrac{2\pi}{3}\ln(2)\\ \dfrac{y_d}{x_d} &= \tan\left(\dfrac{2\pi}{3}\ln(2)\right)\\ y_d &= \tan\left(\dfrac{2\pi}{3}\ln(2)\right) x_d \end{array} Solving for x d x_d , ( x d ) 2 + ( tan ( 2 π 3 ln ( 2 ) ) x d ) 2 = 9 ( x d ) 2 ( 1 + tan 2 ( 2 π 3 ln ( 2 ) ) ) = 9 Factor ( x d ) 2 ( x d ) 2 sec 2 ( 2 π 3 ln ( 2 ) ) = 9 Identity: 1 + tan 2 ( α ) = sec 2 ( α ) ( x d ) 2 = 9 cos 2 ( 2 π 3 ln ( 2 ) ) since 1 sec 2 ( α ) = cos 2 ( α ) x d = 3 cos ( 2 π 3 ln ( 2 ) ) since odd > even , x d > 0 \begin{array}{rlccl} \left(x_d\right)^2 + \left(\tan\left(\dfrac{2\pi}{3}\ln(2)\right)x_d\right)^2 &= 9\\ \left(x_d\right)^2\left(1 + \tan^2\left(\dfrac{2\pi}{3}\ln(2)\right)\right) &= 9 & & & {\color{#3D99F6}\text{Factor }(x_d)^2}\\ \left(x_d\right)^2\sec^2\left(\dfrac{2\pi}{3}\ln(2)\right) &= 9 & & & {\color{#3D99F6}\text{Identity: }1 + \tan^2(\alpha) = \sec^2(\alpha)}\\ \left(x_d\right)^2 &= 9\cos^2\left(\dfrac{2\pi}{3}\ln(2)\right) & & & {\color{#3D99F6}\text{since }\dfrac{1}{\sec^2(\alpha)} = \cos^2(\alpha)}\\ x_d &= 3\cos\left(\dfrac{2\pi}{3}\ln(2)\right) & & & {\color{#3D99F6}\text{since }\sum_{\text{odd}} > \sum_{\text{even}}, x_d > 0}\\ \end{array} So y d = tan ( 2 π 3 ln ( 2 ) ) 3 cos ( 2 π 3 ln ( 2 ) ) = sin ( 2 π 3 ln ( 2 ) ) cos ( 2 π 3 ln ( 2 ) ) 3 cos ( 2 π 3 ln ( 2 ) ) = 3 sin ( 2 π 3 ln ( 2 ) ) \begin{array}{rl} y_d &= \tan\left(\dfrac{2\pi}{3}\ln(2)\right) \cdot 3\cos\left(\dfrac{2\pi}{3}\ln(2)\right)\\ &= \dfrac{\sin\left(\dfrac{2\pi}{3}\ln(2)\right)}{\cos\left(\dfrac{2\pi}{3}\ln(2)\right)} \cdot 3\cos\left(\dfrac{2\pi}{3}\ln(2)\right)\\ &= 3\sin\left(\dfrac{2\pi}{3}\ln(2)\right) \end{array} Therefore, the final displacement between Ash and the starting point is Displacement = ( x d 3 ) 2 + ( y d ) 2 = ( 3 cos ( 2 π 3 ln ( 2 ) ) 3 ) 2 + ( 3 sin ( 2 π 3 ln ( 2 ) ) ) 2 = 9 cos 2 ( 2 π 3 ln ( 2 ) ) 18 cos ( 2 π 3 ln ( 2 ) ) + 9 + 9 sin 2 ( 2 π 3 ln ( 2 ) ) = 9 ( cos 2 ( 2 π 3 ln ( 2 ) ) + sin 2 ( 2 π 3 ln ( 2 ) ) ) + 9 18 cos ( 2 π 3 ln ( 2 ) ) = 9 + 9 18 cos ( 2 π 3 ln ( 2 ) ) since cos 2 ( α ) + sin 2 ( α ) = 1 = 18 18 cos ( 2 π 3 ln ( 2 ) ) \begin{array}{rlccl} \text{Displacement} &= \sqrt{\left(x_d - 3\right)^2 + \left(y_d\right)^2}\\ &= \sqrt{\left(3\cos\left(\dfrac{2\pi}{3}\ln(2)\right) - 3\right)^2 + \left(3\sin\left(\dfrac{2\pi}{3}\ln(2)\right)\right)^2}\\ &= \sqrt{9\cos^2\left(\dfrac{2\pi}{3}\ln(2)\right) - 18\cos\left(\dfrac{2\pi}{3}\ln(2)\right) + 9 + 9\sin^2\left(\dfrac{2\pi}{3}\ln(2)\right)}\\ &= \sqrt{9\left(\cos^2\left(\dfrac{2\pi}{3}\ln(2)\right) + \sin^2\left(\dfrac{2\pi}{3}\ln(2)\right)\right) + 9 - 18\cos\left(\dfrac{2\pi}{3}\ln(2)\right)}\\ &= \sqrt{9 + 9 - 18\cos\left(\dfrac{2\pi}{3}\ln(2)\right)} & & & {\color{#3D99F6}\text{since} \cos^2(\alpha) + \sin^2(\alpha) = 1}\\ &= \sqrt{18 - 18\cos\left(\dfrac{2\pi}{3}\ln(2)\right)} \end{array} Since b = 18 , c = 2 , d = 3 , e = 2 b = 18, c = 2, d = 3, e = 2 , b + c + d + e = 25 b + c + d + e = \boxed{25} .

A really interesting question! Enjoyed solving :)

Thomas Jacob - 4 years, 4 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...